Field study on plasma haptoglobin concentrations and total milk somatic cell counts in cows with untreated and treated mastitis - N.Vasilev; M. Karadaev; I.Fasulkov; F. Ceciliani (Bulgarian Journal of Veterinary Medicine, 2018)
The aim of the present study was to determine plasma haptoglobin concentrations in cows in field conditions. Experiments were carried out a total of 106 cows, divided in 5 groups. The 1st group comprised 25 cows with low milk somatic cell counts (SCC), without microbiological findings used as controls; the IInd group –23 cows with untreated subclinical mastitis with high milk SCC and with-out microbiological findings; the IIIrd group: 13 cows with untreated subclinical mastitis with high milk SCC and with microbiological findings. The IVth group consisted of 17 cows with subclinical mastitis, high milk SCC, microbiological findings, treated with tetracycline HCL 200 mg, neomycin 250 mg, bacitracin 2000 IU, prednisolone 10 mg (Mastijet fort®, MSD Animal Health), and the Vth group – 28 cows with clinical mastitis treated with Mastijet fort®, MSD Animal Health. Our results showed that the mean plasma haptoglobin concentrations in the I (control) group was 0.054±0.003 g/L. In the IInd group (0.288±0.04 g/L) Hp was 5.2 times higher that the mean values of controls (P<0.001). Mean Hp concentration of group III was also statistically significantly different (P<0.001) than that of the control group. The value of Hp in group IV (0.215±0.04 g/L) was significantly lower (P<0.05) that mean values of IInd group but substantially higher (P<0.001) vs controls. The concentra-tion of haptoglobin in cows of the Vth group was statistically significantly lower (P<0.001) compared both with control and IInd groups. In this study, total somatic cell count showed statistically signifi-cant differences (P<0.001) between the control and experimental groups.